User experience evaluation for a bus tracking apps in smart campus initiative - Norazlina Khamis; Kelly Kong Kai Li (Institute of Advanced Engineering and Science, 2021)
Satisfying user experience (UX) is one of the major goals for any application. A good UX will contribute to the higher rate adoption of the application itself. With the emergence of IoT, the concept of smart campus is widely being researched and developed. Smart campus initiative is relatively important as the campus can be considered as a small town by utilizing the same IT infrastructure as smart city. Bus tracking system is one of the initiatives in smart campus environment. One of the main issues is to assess the usability of this apps before it can be deployed widely in campus. This paper will discuss the user experiences evaluation using MeCUE technique on UMS HopIn! a bus tracking apps an initiative towards implementation of smart campus in Universiti Malaysia Sabah. The app gives user the real time location of campus buses and the estimated time of arrival (ETA) for each of the buses. Based on user evaluation it has been found that the application has meet within the expectation with most of the requirements has been fulfilled and the good of UX rating. Thus, the same approach can be applied to support the development of any future smart campus initiative.